The Influence of Nanoparticle on Vaccine Responses against Bacterial Infection - Sareh Bagheri-Josheghani; Bita Bakhshi; Shahin Najar-peerayeh (Journal of Nanotechnology)
Nowadays, nanovaccine is considered as an evolving method in the field of vaccination to induce immunity in the human body against various diseases, including bacterial or viral diseases as well as virulent tumors. Nanovaccines are more efficient than traditional vaccines since they could potentially induce both humoral and cellular immune reactions. Various studies have shown that nanoparticles with multiple compounds have been designed as delivery systems or as adjuvants for vaccines. Nanoparticles could function as a drug delivery tool, as an adjuvant to promote antigen processing, and as an immune modulator to induce immune responses. These nanoparticles generate immune responses through activating immune cells as well as through the production of antibody responses. Design engineering of nanoparticles (NPs) used to produce nanovaccines to induce immunity in the human body needs comprehensive information about the ways they interact with the component of immune system. Challenges remain due to the lack of sufficient and comprehensive information about the nanoparticles' mode of action. Several studies have described the interactions between various classes of nanoparticles and the immune system in the field of prevention of bacterial infections. The results of some studies conducted in recent years on the interaction between nanoparticles and biosystems have considerably affected the methods used to design nanoparticles for medical applications. In this review, NPs’ characteristics influencing their interplay with the immune system were discussed in vivo. The information obtained could lead to the development of strategies for rationalizing the design of nanovaccines in order to achieve optimum induction of immune response.